Unilateral variations in the branching pattern of right external carotid artery - a case report - P Savithri (Wolters Kluwer Medknow Publications, 2012)
A case report of anomalous origin and branching pattern of right external carotid artery found during the dissection of human cadavers is reported here. Knowledge of anatomical variations of external carotid artery is especially important in head & neck surgeries. This knowledge is also important for radiologists in the image interpretation. In the case reported here, the right external carotid artery gave direct origin of one of dorsal lingual artery, two stylomastoid arteries,muscular artery and lymph nodal artery along with its normal eight branches. Generally the dorsal lingual arteries are two arising from lingual artery. Contrary to that, in this case the dorsal lingual arteries were found arising one from front of external carotid artery and other from lingual artery, and both these arteries communicated at 4mm beyond their origin .The two stylomastoid arteries arising directly from the front of external carotid artery 4mm above the facial artery were found arising with a gap of 2mm distance from one another. Muscular artery arose directly from the posterior aspect of external carotid artery opposite the anomalous dorsal lingual artery and descended downwards and forwards in its course giving small twigs to surrounding muscles . Lymph nodal artery arising just beside the muscular artery opposite to facial artery passed downwards and laterally and divided into two small twigs to supply a pair of lymph nodes. These lymph nodes are deep cervical nodes measuring about 5x5 mm in size hard in consistency on histopathological examination, found to be nonmalignant.